Dual exon skipping in myostatin and dystrophin for Duchenne muscular dystrophy - van Ommen Gert Jan B; den Dunnen Johan T; de Gorter David JJ; Terlouw Samuel; van Heiningen Sandra H; Hoogaars Willem MH; Kemaladewi Dwi U; Aartsma-Rus Annemieke; ten Dijke Peter; 't Hoen Peter AC (BMC, 2011)
Abstract Background Myostatin is a potent muscle growth inhibitor that belongs to the Transforming Growth Factor-β (TGF-β) family. Mutations leading to non functional myostatin have been associated with hypermuscularity in several organisms. By contrast, Duchenne muscular dystrophy (DMD) is characterized by a loss of muscle fibers and impaired regeneration. In this study, we aim to knockdown myostatin by means of exon skipping, a technique which has been successfully applied to reframe the genetic defect of dystrophin gene in DMD patients. Methods We targeted myostatin exon 2 using antisense oligonucleotides (AON) in healthy and DMD-derived myotubes cultures. We assessed the exon skipping level, transcriptional expression of myostatin and its target genes, and combined myostatin and several dystrophin AONs. These AONs were also applied in the mdx mice models via intramuscular injections. Results Myostatin AON induced exon 2 skipping in cell cultures and to a lower extent in the mdx mice. It was accompanied by decrease in myostatin mRNA and enhanced MYOG and MYF5 expression. Furthermore, combination of myostatin and dystrophin AONs induced simultaneous skipping of both genes. Conclusions We conclude that two AONs can be used to target two different genes, MSTN and DMD, in a straightforward manner. Targeting multiple ligands of TGF-beta family will be more promising as adjuvant therapies for DMD.